1990
DOI: 10.1038/bjc.1990.178
|View full text |Cite
|
Sign up to set email alerts
|

Dose intensity in cancer chemotherapy

Abstract: There is substantial evidence that, for the majority of antitumour agents including alkylating agents, anthracycline antibiotics and anti-metabolites, there is a steep dose response curve when these agents are studied in in vitro and in vivo models (Griswold et al., 1963;Bruce et al., 1966;Schabel et al., 1984). It is this dose-response relationship which is often cited in support of high dose chemotherapy with autologous bone marrow rescue as a promising avenue for the treatment of solid tumours. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Factors involving blood tests were examined immediately prior to chemotherapy. The relative dose intensity (RDI) of GEM was calculated according to the method described by Dodwell et al [24].…”
Section: Clinical Data and Neutropeniamentioning
confidence: 99%
“…Factors involving blood tests were examined immediately prior to chemotherapy. The relative dose intensity (RDI) of GEM was calculated according to the method described by Dodwell et al [24].…”
Section: Clinical Data and Neutropeniamentioning
confidence: 99%
“…Studies analyzing the results obtained in locally advanced disease separately report even higher response rates of up to 69% in this subset of patients [39]. Retrospective analyses of several tumor types have suggested that the dose intensity of chemotherapy may be important [8,20]. However, the results of prospective randomized studies addressing cisplatin dose intensity in NSCLC are inconclusive.…”
Section: Toxicitymentioning
confidence: 99%
“…It is tempting to speculate that the increase in dose intensity has contrib uted to the conversion of partial into complete remis sions. A number of retrospective studies of different types of tumor and SCLC has demonstrated that dose intensity is significantly correlated with the clinical outcome [33,41], Also, accelerated weekly chemotherapy may result in a prolongation of survival as recently described by Miles et al [42] and Murray et al [18], In a recent prospective randomized trial by Woll et al [43] patients received VICE chemotherapy with or without G-CSF support. No treatment intervals were defined and retreatment was based on WBC and platelet recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Although no optimal regimen has been identified combinations containing cisplatin, carboplatin, etoposide, doxorubicin, or ifosfamide have been demon- (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 20 All cycles 28 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) 23 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) 21 (20)(21)(22)(23)(24)(25)(26)(27)…”
Section: Discussionmentioning
confidence: 99%